Notch Signaling Pathway Was Involved in Regulating Programmed Cell Death 1 Expression during Sepsis-Induced Immunosuppression. (30th April 2015) - Pan, Tingting; Liu, Zhaojun; Yin, Jianyong; Zhou, Tianyun; Liu, Jialin; Qu, Hongping
Abstract : Programmed cell death 1 (PD-1) plays an important pathologic role in sepsis-induced immunosuppression. However, whether PD-1 overexpression occurs early during septic shock is unknown and its regulation mechanism is also unknown. Our study investigated the expressions of PD-1/programmed death-ligand 1 (PD-L1) on immune cells in peripheral blood from the early-stage septic shock patients. We found that both PD-1 and PD-L1 showed increased expressions on the CD4 + T cells and monocytes. It indicated that PD-1 expression might be an early biomarker to assess illness severity and predict the prognosis of septic shock. Then, we further investigated the mechanism underlying the regulation of PD-1 expression. Our data showed that Notch signaling pathway was activated in both septic shock patients and lipopolysaccharide- (LPS-) tolerant THP1 cells and both interleukin-10 (IL-10) and PD-1 were increased in the THP1 cells. Inhibition of Notch signaling by N-[N-(3, 5-difluorophenacetyl)-L-alanyl]-S-phenyl glycinet-butyl ester (DAPT) induced significantly decreased expressions of PD-1 and IL-10 in the LPS-tolerant cell model. Our work suggested that Notch signaling pathway was involved in the regulation of PD-1 expression.